2015
DOI: 10.1590/1519-6984.01914
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two Brazilian indigenous plants for phytostabilization and phytoremediation of copper-contaminated soils

Abstract: Indigenous plants have been grown naturally and vigorously in copper contaminated soils. Thus, the aim of this study was to evaluate the phytoremediation ability of two indigenous plants naturally grown in two vineyard soils copper contaminated, and in a copper mining waste. However, it was evaluated the macro and micronutrient uptake and the potential of phytoremediation. So, a greenhouse study was carried out with Bidens pilosa and Plantago lanceolata in samples of vineyard soils (Inceptisol and Mollisol) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…In this context, the potential of B. trimera and B. dracunculifolia in the removal of heavy metals contained in contaminated soils is higher than those found by Andreazza et al [65] [69].…”
Section: Phytoremediation Indexmentioning
confidence: 71%
“…In this context, the potential of B. trimera and B. dracunculifolia in the removal of heavy metals contained in contaminated soils is higher than those found by Andreazza et al [65] [69].…”
Section: Phytoremediation Indexmentioning
confidence: 71%
“…Nevertheless, the translocation factor (TF) of Cu was correlated negatively with the stem diameter (-0.81) and the biomass of the roots (-0.75). Cu is an essential micronutrient, even though it can be toxic above certain levels (Barbosa et al 2013;Andreazza et al 2015;Silva et al 2015). Cadmium (Cd) in the shoots of sunflower had negative correlations with stem diameter (-0.69) and the biomass production of the roots (-0.63).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the strategies employed in phytostabilization, plants that can appropriately fall under this mechanism is their ability to tolerate and immobilize metals and other contaminants, low translocation capacity from root to plant aerial parts and of course extensive and fibrous tap root system [7]. Among several studies that reported plants species with these characteristics [47][48][49] demonstrating the phytostabilization of Zn, Pb, Cu and Cd by different plants in soil and sediment polluted environments.…”
Section: Phytostabilizationmentioning
confidence: 99%